Porphyromonas gingivalis Administration Induces Gestational Obesity, Alters Gene Expression in the Liver and Brown Adipose Tissue in Pregnant Mice, and Causes Underweight in Fetuses - Yoshida, Sumiko; Hatasa, Masahiro; Ohsugi, Yujin; Tsuchiya, Yosuke; Liu, Anhao; Niimi, Hiromi; Morita, Kazuki; Shimohira, Tsuyoshi; Sasaki, Naoki; Maekawa, Shogo; Shiba, Takahiko; Hirota, Tomomitsu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Preventing adverse pregnancy outcomes is crucial for maternal and child health. Periodontal disease is a risk factor for many systemic diseases including adverse pregnancy outcomes, such as preterm birth and low birth weight. In addition, the administration of the periodontopathic bacterium Porphyromonas gingivalis exacerbates obesity, glucose tolerance, and hepatic steatosis and alters endocrine function in the brown adipose tissue (BAT). However, the effects of having periodontal disease during pregnancy remain unclear. Thus, this study investigates the effect of P. gingivalis administration on obesity, liver, and BAT during pregnancy. Sonicated P. gingivalis (Pg) or saline (Co) was injected intravenously and administered orally to pregnant C57BL/6J mice three times per week. Maternal body weight and fetal body weight on embryonic day (ED) 18 were evaluated. Microarray analysis and qPCR in the liver and BAT and hepatic and plasma triglyceride quantification were performed on dams at ED 18. The body weight of Pg dams was heavier than that of Co dams; however, the fetal body weight was decreased in the offspring of Pg dams. Microarray analysis revealed 254 and 53 differentially expressed genes in the liver and BAT, respectively. Gene set enrichment analysis exhibited the downregulation of fatty acid metabolism gene set in the liver and estrogen response early/late gene sets in the BAT, whereas inflammatory response and IL6/JAK/STAT3 signaling gene sets were upregulated both in the liver and BAT. The downregulation of expression levels of Lpin1, Lpin2, and Lxra in the liver, which are associated with triglyceride synthesis, and a decreasing trend in hepatic triglyceride of Pg dams were observed. P. gingivalis administration may alter lipid metabolism in the liver. Overall, the intravenous and oral administration of sonicated P. gingivalis-induced obesity and modified gene expression in the liver and BAT in pregnant mice and caused fetuses to be underweight.